Introduction to Buddhism in Contemporary Lithuania: Groups and Their Activity - Laudere, Marika (Religion and society in Central and Eastern Europe, 2013)
After the collapse of the USSR, new religious ideas have appeared in Post-Soviet countries. People have started to become involved in religious groups that were not previously active in these regions. Lithuania is not an exception. This study is based on the field work in Buddhist groups (2012 - 2013), and attempts to document the development of Buddhism in Lithuania by investigating several Buddhist groups and their activity in contemporary Lithuania.